The Special Data Dissemination Standard : Guide for Subscribers and Users. (Manuals and Guides, 2008)
The Special Data Dissemination Standard (SDDS) was established by the IMF in 1996 to guide members that already had, or that might seek, access to international capital markets in providing key economic and financial data to the public. In the following year, the IMF established the General Data Dissemination Standard (GDDS), which seeks to prepare countries for meeting the requirements of the SDDS. Data supplied by countries subscribing to the SDDS, as well as information provided by countries participating in the GDDS, are posted on the Dissemination Standards Bulletin Board (DSBB) on the IMF's public website (http://dsbb.imf.org). This Guide is intended to assist subscribers of the SDDS, GDDS participants moving toward subscription to the SDDS, and users of the DSBB in becoming aware of the features and scope of the SDDS and the DSBB. It is intended to further the IMF's initiatives in data transparency and standards, to enhance the public availability of timely and comprehensive international statistics, and therefore to contribute to countries pursuit of sound macroeconomic policies and to the improved functioning of global financial markets.